Transformasi Manajemen Koperasi Syariah sebagai Strategi Penguatan Ekonomi Umat di Tengah Perubahan Perekonomian Negara Muslim - Ali Achmad Muhajir; Mohammad Ridwan; Dini Selasi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the transformation of Islamic cooperative management as a strategy for strengthening the Muslim community's economy amid the changing economic landscape of Muslim countries. Global economic dynamics characterized by digitalization, the rapid growth of the halal industry, increasing competition among financial institutions, and economic uncertainty have encouraged Islamic cooperatives to transform in order to remain adaptive and competitive. This research employed a qualitative method using a library research approach by examining relevant regulations, scientific articles, books, and other scholarly documents. The collected data were analyzed using content analysis, comparative analysis, and descriptive qualitative analysis. The findings indicate that the transformation of Islamic cooperative management should focus on strengthening governance through Good Cooperative Governance, accelerating digital transformation, improving human resource quality, developing innovative products and services, and enhancing collaboration within the Islamic economic ecosystem. Although Islamic cooperatives continue to face challenges related to human resource quality, capital limitations, technological adoption, and regulatory support, they possess significant potential to empower the Muslim community through MSME financing, Islamic financial literacy enhancement, and community-based economic development. Therefore, a sustainable management transformation model is essential for improving the competitiveness of Islamic cooperatives while strengthening the economic resilience of the Muslim community amid the evolving economic conditions of Muslim countries.